2002
DOI: 10.1515/bc.2002.146
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Cathepsin B Expression May Offer Additional Prognostic Information for Ovarian Cancer Patients

Abstract: The lysosomal cysteine proteinase cathepsin B has been implicated in the progression of various human tumors including ovarian cancer. Included in this study were 63 patients with epithelial ovarian carcinoma. Follow-up information (median follow-up period 7 years) was available for all patients, among whom 42 (66.7%) had relapsed and 32 (50.8%) had died. The immunohistochemistry method was adopted for the detection of cathepsin B using paraffin embedded specimens. Results were compared to clinico-pathological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 16 publications
(10 reference statements)
3
29
0
1
Order By: Relevance
“…M17S2 is a surface marker in ovarian cancer (25), and the expression of M17S2 was found to be inversely correlated to the survival in renal cell carcinoma patients (26). Cathepsin B is a lysosomal cysteine protease, and the overexpression of cathepsin B has been associated with ovarian cancer, adenocarcinoma, and other tumors (27). The ability of these proteins to inhibit p53 activity may underlie these correlations to oncogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…M17S2 is a surface marker in ovarian cancer (25), and the expression of M17S2 was found to be inversely correlated to the survival in renal cell carcinoma patients (26). Cathepsin B is a lysosomal cysteine protease, and the overexpression of cathepsin B has been associated with ovarian cancer, adenocarcinoma, and other tumors (27). The ability of these proteins to inhibit p53 activity may underlie these correlations to oncogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…A role of CTSB and CTSL in tumor cell invasion was suggested by the observation of the increased invasiveness of cells overexpressing CTSB and CTSL (17) and by the decreased invasion in the presence of specific inhibitors of CTSB and CTSL (18). Moreover, immunohistochemical analysis demonstrated that CTSB and CTSL exist in the cytoplasm of tumor cells in human ovarian cancer (9,19). Similarly, in the present study increased expression of CTSB and CTSL was noted in cancer, but not normal ovarian tissue, suggesting that CTSB and CTSL are survival prognostic factors in ovarian cancer, and may contribute to the invasiveness of ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to interacting with other proteases, CTSB may regulate the activity of kinase signaling networks, cell surface receptors, and signaling molecules such as chemokines, cytokines and growth factors (25). However, such interactions are usually bidirectional because kinases can also regulate many proteases through phosphorylation while proteases can control the actions of a multitude of kinases (21).High expression levels of CTSB have been linked to aggressiveness and poor prognosis in several cancers, such as colorectal and ovarian carcinomas (15,29,34,37,38). Compared to the amount…”
mentioning
confidence: 99%
“…High expression levels of CTSB have been linked to aggressiveness and poor prognosis in several cancers, such as colorectal and ovarian carcinomas (15,29,34,37,38). Compared to the amount…”
mentioning
confidence: 99%